Feminist Organizations and Intersectionality: Contesting Hegemonic Feminism - Bunjun, Benita (Atlantis, 2010)
This paper is a theoretical examination of the foundational ideologies of hegemonic feminism which continue to be contested by feminists engaging with intersectional frameworks and analyses both within the women's movement(s) and feminist organizations in North America. The paper additionally discusses the structures and processes of feminist collectives while drawing on the author's current research on Vancouver Status of Women.